Clinical psychology : Science, practice, and culture - Pomerantz, Andrew M. (Los Angeles, California : Sage, 2014)
The first and second editions of this text were enthusiastically received by both instructors and students. We were please to learn that they found numerous components of the books - its emphasis on issues of culture, its unique pedagogical features, its scholarly yet readable style, its many clinical examples, its balanced approach, and its ancillary package, among others - beneficial to student learning.
Introduction clinical psychology -- Assessment -- Psychotherapy -- Special topics.
Includes bibliographical references and index.
Keywords: CLINICAL PSYCHOLOGY